Identifying synchronization between flow boiling inside two parallel minichannels using joint recurrence plots - Grzybowski Hubert; Gruszczyńska Iwona; Mosdorf Romuald (MATEC Web of Conferences, 2018)
In this study the flow boiling inside two parallel tubes with a diameter of 1 mm was analysed in order to determine synchronization level between the channels. An experimental setup was built to investigate the pressure and temperature oscillation in parallel minichannels. During the experiments, the two-phase flow patterns were recorded by high speed camera and also the presence of vapour in channel outlet was measured by laser-phototransistor sensor. Various types of two-phase flow instabilities were observed in investigated the system. Experiment was carried out for various heat rate and mass flux. The method of identifying synchronization between flow boiling between parallel channel will be presented on measurement data recorded for heat rate q equal to 50.15 W and the average mass flux ṁ equal to 38.8 kg/m2s. The signal was subjected to a nonlinear analysis based on the joint recurrence plot (JRP) method. The JRP method was carried out in order to determine synchronization level between signals from parallel channels. Results of pressure and laser-phototransistor oscillation analysis shows that during flow boiling phase synchronization and phase shift between the channels can be detected using appropriate RQA indicators.